Burlesque West : showgirls, sex and sin in postwar Vancouver - Ross, Becki, 1959- (University of Toronto Press, 2009)
"After the Second World War, Vancouver emerged as a hotbed of striptease talent. In Burlesque West, the first critical history of the city's notorious striptease scene, Becki Ross delves into the erotic entertainment industry at the northern end of the dancers' west coast tour - the North-South route from Los Angeles to Vancouver - which provided rotating work for dancers and variety for club clientele. Lavishly illustrated and thoroughly documented, Burlesque West is an ambitious and engaging social history that looks at the convergence of the personal and the political in a phenomenon that combines sex, art and entertainment, and commerce."--Jacket